Simulation and laboratory test results of 3D CMS pixel detectors for HL-LHC - Alagoz, E; Bubna, M; Krzywda, A; Dalla Betta, G; Povoli, M; Obertino, M; Solano, A; Vilela Pereirah, A; Arndt, K; Bolla, G; Bortoletto, D; Boscardin, M; et al. (2012)
The CMS pixel detector is the innermost tracking device at the LHC, reconstructing interaction vertices and charged particle trajectories. The current planar sensors located in the innermost layer of the pixel detector will be exposed to very high fluences which will degrade their performances. As a possible replacement for planar pixel sensors in the High Luminosity-LHC (HL-LHC), 3D silicon technology is under consideration due to its expected good performance in harsh radiation environments. Studies are also in progress for using 3D silicon pixel detectors in near-beam proton spectrometers at the LHC. Deep Reactive Ion Etching (DRIE) plays a key role in fabricating 3D silicon detectors in which readout and ohmic electrodes are processed through the silicon substrate instead of being implanted on the silicon surface. 3D pixel devices considered in this study were processed at FBK (Trento, Italy), bump bonded to the CMS pixel readout chip, and characterized in the laboratory. Numerical simulations were also carried out. We report on selected results from laboratory measurements and TCAD simulations. © 2012 IOP Publishing Ltd and Sissa Medialab srl.